The effectiveness of a blended-learning training methodology on the dialysis nurse's perception of competence. Quasi-experimental study - Marco Heleno; Pedro Sousa; Fernando Mata (Sociedad Española de Enfermería Nefrológica, 2024)
Introduction: Nurses providing care to individuals with chronic kidney disease undergoing hemodialysis must have specific training in dialysis techniques. Therefore, Dialysis Nurses should develop specific and differentiated competencies throughout their professional career. Blended learning plays a fundamental role in modernizing education, making it more accessible, flexible, and tailored to the needs of nurses. It offers opportunities to improve the quality of learning and promote collaboration and innovation in the educational process. Objectives: The study's objectives were to assess the influence of sociodemographic variables (age and education) and acquired training (frequency and duration) on the competence profile and to evaluate the effectiveness of a training program in HD techniques on the perception of competence of Dialysis Nurses. Material and Methods: Quasi-experimental, pre and post-test study without a control group. Results: Age, frequency, and duration of training influence dialysis nurses' perceptions of competence. Participants showed a significant improvement in some domains of dialysis nurses' perceptions of competence after the implementation of a training program in HD techniques. Conclusions: A properly structured and standardized training program for dialysis nurses is an asset in acquiring, consolidating, and updating knowledge.